Pseudo-Period of Distorted Lattices in Disordered Solids - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
Disordered lattices are discussed in terms of the spacing between adjacent atoms. This discussion is based on the randomness of the above spacing and on the crystalline potential by assuming a one-dimensional solid. Our theoretical considerations are useful to study certain aspects of amorphous semiconductors.